2008
DOI: 10.1016/j.jacc.2007.09.058
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Osteoprotegerin Levels and Long-Term Prognosis in Patients With Acute Coronary Syndromes

Abstract: Serum OPG is strongly predictive of long-term mortality and HF development in patients with ACS, independent of conventional risk markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
156
3
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 185 publications
(172 citation statements)
references
References 26 publications
11
156
3
2
Order By: Relevance
“…Differences compared with our previous report in 897 patients with ACS, in whom an association between high osteoprotegerin levels at admission and all‐cause mortality was observed, could also be attributable to the markedly longer follow‐up time (89 months) and, thus, a larger proportion and incidence of fatalities 17. Nonetheless, similar to the present study, the relationship between osteoprotegerin and MI was not significant in adjusted analysis 17. Also, in a study by Roysland et al, who evaluated osteoprotegerin in 4463 patients with non‐STE ACS with a similar follow‐up as our study,16 the association with MI was not present in adjusted analysis, although an association with cardiovascular death persisted in adjusted analysis.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…Differences compared with our previous report in 897 patients with ACS, in whom an association between high osteoprotegerin levels at admission and all‐cause mortality was observed, could also be attributable to the markedly longer follow‐up time (89 months) and, thus, a larger proportion and incidence of fatalities 17. Nonetheless, similar to the present study, the relationship between osteoprotegerin and MI was not significant in adjusted analysis 17. Also, in a study by Roysland et al, who evaluated osteoprotegerin in 4463 patients with non‐STE ACS with a similar follow‐up as our study,16 the association with MI was not present in adjusted analysis, although an association with cardiovascular death persisted in adjusted analysis.…”
Section: Discussioncontrasting
confidence: 93%
“…At 1 month, hs‐CRP and, in particular, GDF‐15 were among the strongest predictors of osteoprotegerin; they are more closely related to adverse cardiovascular outcomes in our cohort and could, therefore, partly explain the lack of association with outcomes, compared with other studies that lack GDF‐15 measurements. Differences compared with our previous report in 897 patients with ACS, in whom an association between high osteoprotegerin levels at admission and all‐cause mortality was observed, could also be attributable to the markedly longer follow‐up time (89 months) and, thus, a larger proportion and incidence of fatalities 17. Nonetheless, similar to the present study, the relationship between osteoprotegerin and MI was not significant in adjusted analysis 17.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Studies showed that OPG was an independent predictor of cardiovascular disease (Nybo and Rasmussen 2008; Omland et al. 2008). The previous study reported that rs2073617 C/C and rs2073618 C/C variant genotypes of the OPG gene were significantly and independently associated with the increased risk of ischemic stroke in an Italian population with diabetic patients (Biscetti et al.…”
Section: Discussionmentioning
confidence: 99%